Living digital 2040: Future of work, education, and healthcare - POON, King Wang (Institutional Knowledge at Singapore Management University, 2017)
Countries, cities, and companies are investing in smart cities and digital economies. How can people thrive as their lives are disrupted and transformed? Will jobs be created or destroyed? Will digital divides narrow or widen in education and healthcare? Living Digital 2040 provides practical answers to these questions. It focuses on the future of work, education, and healthcare, because all of us experience these three social and economic institutions every day, and at seminal stages of our lives. Work, education, and healthcare also build our capabilities and relationships, so that we can live flourishing lives. Living Digital 2040 takes the view that it is up to us create a future that is better than the one today. It explores practical possibilities we could pursue, and how our collective capacity for innovation and collaboration can tackle the disruptive forces, and transform our lives for the better.